Euclid’s elements publication in Vilnius - Banionis, Juozas (Lietuvos matematikos rinkinys, 2021)
200 years ago in Vilnius the famous Elements by Euclid was set in print in the Polish language. The translationwas made by professorof mathematics Jozef Czech (1762–1810) and published in J. Zawadski’s printing house in 1807. This publication consisted of 8 books, i.e., the first six, eleventh and twelfth books on planimetry and stereometry. In 1817 the Elements was published once more. The fact that Euclid’s Elements appeared in print inVilnius can be discussedfrom two viewpoints. First, the society of the former Commonwealth of the Two Nations could get access to the heritage of antiquity. Second, the treatise was translated and published later then in other European countries. As a result, the Elements did not become the only textbook on geometry.